Mengembalikan Peran Keluarga sebagai Agen Pendidikan Iman di Masa COVID-19 - L. B., Julianti; Limbong, Deborah Christina Vallery (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2023)
The COVID-19 pandemic has brought significant changes to family, church, and educational life, including Christian Religious Education (CRE). Social restrictions and the shift of activities into domestic spaces have restored the family’s central role in faith education. This article examines the importance of reestablishing the family as the primary agent of faith formation during the pandemic, using a qualitative-descriptive approach and a theological-pedagogical literature review. The findings show that the family is the first community in shaping children’s spirituality, although this role had often been delegated to churches and formal educational institutions before the pandemic. The pandemic created opportunities for parents to become more actively involved in nurturing faith through family worship, prayer, Bible reading, and daily life examples. Strengthening the family’s function not only supports children’s spiritual growth but also strengthens family relationships amid crises. Therefore, churches and Christian education institutions need to develop mentoring models that empower families as primary partners in faith education and Christian character formation.   Abstrak Pandemi COVID-19 membawa perubahan besar dalam kehidupan keluarga, gereja, dan pendidikan, termasuk Pendidikan Agama Kristen (PAK). Pembatasan sosial dan peralihan aktivitas ke ruang domestik menjadikan keluarga kembali berperan sentral dalam pendidikan iman. Artikel ini mengkaji pentingnya mengembalikan keluarga sebagai agen utama pendidikan iman di masa pandemi melalui pendekatan kualitatif-deskriptif dan studi literatur teologis-pedagogis. Hasil penelitian menunjukkan bahwa keluarga merupakan komunitas pertama dalam pembentukan spiritualitas anak, meskipun sebelumnya peran tersebut sering diserahkan kepada gereja dan sekolah. Pandemi membuka peluang bagi orang tua untuk lebih aktif membina iman melalui ibadah keluarga, doa bersama, pembacaan Alkitab, dan keteladanan hidup. Penguatan fungsi keluarga tidak hanya mendukung pertumbuhan spiritual anak, tetapi juga mempererat relasi keluarga di tengah krisis. Karena itu, gereja dan lembaga PAK perlu membangun model pendampingan yang memberdayakan keluarga sebagai mitra utama pendidikan iman dan pembentukan karakter Kristiani.